2021
DOI: 10.1002/eng2.12396
|View full text |Cite
|
Sign up to set email alerts
|

An aerial robotic system for inventory of stockpile warehouses

Abstract: This article describes the development and evaluation of an aerial robotic system for smart inventory of stockpile warehouses. The system was developed to automatically measure piles of different bulk materials, such as phosphorus and potassium compounds, which are stored in bays of different sizes inside a warehouse. This warehouse configuration is very common among fertilizer and animal food industries in Brazil. While an inventory can be executed by a human technician, the insalubrious environment, the impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Drone scanning involves the use of unmanned aerial vehicles (UAVs) equipped with cameras or laser scanners to perform aerial scans of coal piles [8][9][10][11]. This system can rapidly capture surface data of extensive coal piles within a short timeframe, thereby offering the advantages of improved resolution and comprehensiveness.…”
Section: D Reconstruction Of Coal Pilesmentioning
confidence: 99%
“…Drone scanning involves the use of unmanned aerial vehicles (UAVs) equipped with cameras or laser scanners to perform aerial scans of coal piles [8][9][10][11]. This system can rapidly capture surface data of extensive coal piles within a short timeframe, thereby offering the advantages of improved resolution and comprehensiveness.…”
Section: D Reconstruction Of Coal Pilesmentioning
confidence: 99%
“…This study aimed to examine the accuracy of measuring stockpile volumes using UAVs. The objectives of the research were to assess errors in field measurements and high-precision volume calculations, to map the volume of stockpiles [19] using UAV images, and to calculate the time needed for the survey. The imaging process was performed using a UAV, while the detailed survey was carried out through Laser Scanning to compare and verify the accuracy of both methods.…”
Section: Mapping Implementationmentioning
confidence: 99%
“…Recently, multirotor drones have been employed in numerous applications involving confined space inspection, including stockpile volume estimation, e.g., [1,97,98]. Multirotor drones, in particular, possess the ability to hover and fly in all directions, making them well-suited for indoor missions.…”
Section: Optimizing Drone Solutionsmentioning
confidence: 99%
“…This is besides the fact that vision-based approaches are not favored in dark environments. Gago et al [98] demonstrated the development and evaluation of an aerial robotic system for stockpile volume estimation within warehouses. They used a DJI Matrice 100 quadrotor drone and equipped it with a 3D LiDAR (Velodyne VLP 16 Puck Lite).…”
Section: Optimizing Drone Solutionsmentioning
confidence: 99%